The Optimal Distribution of Reactive Power on Synchronous Generators in Power Plants. (2015) - Atănăsoae, Pavel; Pentiuc, Radu; Hopulele, Eugen
Abstract: In the present conditions of operation of the electricity market, the production and consumption of reactive power by the synchronous generators in power plants shows a special importance. The paper analyzes the possibility of optimal distribution of reactive power on the synchronous generators in the case of a combined heat and power plant with 60 MW turbogenerators. The optimization problem consists in the distribution of reactive power on the synchronous generators in the power plant, knowing the reactive power exchanged with the local distribution network operator, so that the total losses of active power due to the reactive power flow in the power plant to be minimal.